Gram‐Positive and Gram‐Negative Antibiotic Activity of Asymmetric and Monomeric Robenidine Analogues. (19th November 2018) - Russell, Cecilia C.; Stevens, Andrew; Pi, Hongfei; Khazandi, Manouchehr; Ogunniyi, Abiodun D.; Young, Kelly A.; Baker, Jennifer R.; McCluskey, Siobhann N.; Page, Stephen W.; Trott, Darren J.; McCluskey, Adam
Abstract: Desymmetrisation of robenidine (1 : N ′, 2‐bis(( E )‐4‐chlorobenzylidene)hydrazine‐1‐carboximidhydrazide) and the introduction of imine alkyl substituents gave good antibiotic activity. Of note was the increased potency of two analogues against vancomycin‐resistant Enterococci (VRE), one of which returned a MIC of 0.5 μg mL −1 . Five analogues were found to be equipotent or more potent than the lead1 . Introduction of an indole moiety resulted in the most active robenidine analogue against methicillin‐resistant S. aureus (MRSA), with a MIC of 1.0 μg mL −1 . Imine C=NH isosteres (C=O/C=S) were inactive. Monomeric analogues were 16–64 μg mL −1 active against MRSA and VRE. An analogue that lacks the terminal hydrazide NH moiety showed modest Gram‐negative activity at 64 μg mL −1 . A 4‐ tert ‐butyl analogue was shown to be active against both Gram‐positive and ‐negative strains at 16–64 μg mL −1 . In general, additional modifications with aromatic moieties was poorly tolerated, except with concomitant introduction of an imine C‐alkyl group. The activity of these analogues against MRSA and VRE ranged from 8 μg mL −1 to inactive (MIC>128 μg mL −1 ) with the naphthyl and indole analogues. Gram‐negative activity was most promising with two compounds at 16 μg mL −1 against E. coli . Against P. aeruginosa, the highest activity observed was with MIC values of 32 μg mL −1 with another two analogues. Combined, these findings support the further development of the ( E )‐2‐benzylidenehydrazine‐1‐carboximidamide scaffold as a promising scaffold for the development of antibiotics against Gram‐positive and Gram‐negative strains. Abstract : Repurposing robenidine leads to novel Gram‐positive and Gram‐negative agents with activity against methicillin‐resistant S. aureus (MRSA), vancomycin‐resistant Enterococci (VRE), E. coli and P. aeruginosa . The most promising analogues return MIC values in the range of 0.5–16 μg mL −1 against Gram‐positive MRSA and VRE; against the Gram‐negative E. coli and P. aeruginosa, MIC values of 16 and 32 μg mL −1 were noted.